Variabilidade acústica nos botos-cinza (Sotalia guianensis, Van Benédén, 1864) - Lopes, Nara Pavan (Brasil, 2016)
In communication a signal is transmitted by a sender and can carry information about its identity, size, sexual status, ability to fight and to survive. Multiple factors can interfere with this communication, varying the output signal as a result of variation in the environment, body size, social learning and cultural transmission. Acoustic signals may vary within species between populations. Dialects are signal variations of two populations that can exchange genes and geographic variation micro- or macro-geographic, depending on the distance, occurs when individuals from different populations don’t mix. These terms are not well established in the literature and are often considered the same or used errouneously, thus a revision was made to clarify the terms involved in acoustic variation. A standardization of terms is proposed and clear deffinitions presented based on the processes that may or may not be related to the evolution of variability. Odontocetes (toothed whales, Order Cetartiodactyla) use acoustic communication in the mediation of social interactions, to obtain food and to navigate. One of the main sounds produced by dolphins in their interactions is the whistle (frequency modulated tonal sound). This study aimed to compare whistles of estuarine dolphins (Sotalia guianensis) collected in Baía Formosa, RN (6o 22' S; 35° 00' W) with published data from other sites in Latin America. The results show significant correlations between maximum and end frequencies as well as between initial and minimum frequencies in Baía Formosa as well as in all other places, indicating a preponderance of frequency ascending whistles used by the species along its distribution. The duration had a significant negative correlation with the initial frequency at all locations tested (p <0.00001 and r = 0.71) and suggests a physiological threshold for high frequency whistles. The principal component analysis divided sites into two major groups, but the discrimination was not related to latitudinal variation. Sampling ...